EFFORTS TO IMPROVE STUDENTS’ MATHEMATICAL PROBLEM SOLVING ABILITY THROUGH CONTEXTUAL TEACHING AND LEARNING AT SMP NEGERI 1 BINJAI - Desy Agustina Situngkir; E Elvis Napitupulu (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2017)
ABSTRACT The purpose of this research was to know whether contextual teaching and learning (CTL) approach could improve students’ mathematical problem solving ability (SMPSA) in eighth grade of SMP Negeri 1 Binjai. The type of this research was Classroom Action Research. The subject of this research was students in class VIII-9 which consisted of 20 students. The object was SMPSA on cube and cuboid topic in eighth grade of SMP Negeri 1 Binjai Academic Year 2015/2016.This study consisted of two cycles.  Each cycle had two meetings. SMPSA was tested in the end of cycle. Instrument used to collect data in this research were test and observation sheet. After giving a treatment to students, in the first cycle, the average score of their mathematical problem solving ability was 2.30. Ten of  20 students (50%) obtained score ³ 2.67. The average score of teacher’s activities in observation sheet was 2.66, which classified as good category. The average score of students’ activities in observation sheet was 2.55, which classified as good category. In the second cycle, the average score of mathematical problem solving ability was increased became 3.05 with 18 students (90%) obtained score ³ 2.67. The average score of teacher’s activities in observation sheet was 3.44, which classified as very good category. The average score of students’ activities in observation sheet was 3.22, which classified as very good category. From the result of research, it can be concluded that the implementation of contextual teaching and learning (CTL) approach can improve students’ problem solving ability. The suggestion that given for teachers is to be able to implement contextual teaching and learning (CTL) approach as an alternative in learning process that can improve problem solving ability.Keywords : Contextual Learning, Mathematical Problem solving Ability